2021
DOI: 10.3390/ani11020314
|View full text |Cite
|
Sign up to set email alerts
|

Lactation Associated Genes Revealed in Holstein Dairy Cows by Weighted Gene Co-Expression Network Analysis (WGCNA)

Abstract: Weighted gene coexpression network analysis (WGCNA) is a novel approach that can quickly analyze the relationships between genes and traits. In this study, the milk yield, lactose, fat, and protein of Holstein dairy cows were detected in a lactation cycle. Meanwhile, a total of 18 gene expression profiles were detected using mammary glands from six lactation stages (day 7 to calving, −7 d; day 30 post-calving, 30 d; day 90 post-calving, 90 d; day 180 post-calving, 180 d; day 270 post-calving, 270 d; day 315 po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…It was shown that UFM1-specific ligase 1 mediates the expression of genes related to milk fat synthesis through the MAP signaling pathway in mouse mammary epithelial cells (Kuang et al, 2020). Phingolipids (Fan et al, 2021) and the p53 signaling pathway (Li et al, 2020) were also potential candidates for milk fat synthesis; thus, targeting the core_lncRNAs of these target genes in milk fat metabolism is not negligible.…”
Section: F I G U R E 5 Functional Enrichment Analysis Of Core_lncrna ...mentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that UFM1-specific ligase 1 mediates the expression of genes related to milk fat synthesis through the MAP signaling pathway in mouse mammary epithelial cells (Kuang et al, 2020). Phingolipids (Fan et al, 2021) and the p53 signaling pathway (Li et al, 2020) were also potential candidates for milk fat synthesis; thus, targeting the core_lncRNAs of these target genes in milk fat metabolism is not negligible.…”
Section: F I G U R E 5 Functional Enrichment Analysis Of Core_lncrna ...mentioning
confidence: 99%
“…WGCNA can be used to analyze data on complex processes and plays a crucial role in exploring the characteristics of gene networks associated with complex traits (Bordini et al, 2021; Jia et al, 2020; Yao et al, 2019). In the last 2 years, scholars have used WGCNA to study mammary gland functional characteristics and lactation properties in ruminants (Deng et al, 2019; Fan et al, 2021). However, the application of WGCNA of lncRNAs to milk fat metabolism in dairy cows has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Breeding researchers have identified a range of potent genes and biomarkers in milk fat metabolism with the widespread use of next-generation sequencing technologies and the dramatic reduction in sequencing costs 7 . Despite the transcriptome determining the characteristic of spatial and temporal specificity, there is less linkage to phenotypic data 8 . Weighted gene co-expression network analysis (WGCNA) can combine gene expression with phenotypic data 9 , 10 and gather genes with similar expression patterns into one module 11 .…”
Section: Introductionmentioning
confidence: 99%
“…It takes advantage of a graph theoretical approach to understanding correlations amongst genes and grouping genes into modules that typically have coordinated biological functions and regulatory mechanisms [ 14 ]. Currently, WGCNA has been extensively used to construct gene co-expression networks and identify centrally connected hub genes in humans, animals and plants [ 14 , 15 , 16 ]. However, this method is rarely applied to plant pathogens.…”
Section: Introductionmentioning
confidence: 99%